2019
DOI: 10.3920/wmj2018.2425
|View full text |Cite
|
Sign up to set email alerts
|

Monascus spp. used in wheat kernel solid-state fermentations: growth, extrolite production and citrinin cytotoxicity

Abstract: Monascus fermentation products can be consumed as food or feed supplements or used as food colouring or flavouring agents. In this study, qPCR and Q-TOF LC/MS methods were developed to monitor Monascus ruber and Monascus purpureus growth and extrolite (lovastatin, mevastatin, as well as the regulated mycotoxin, citrinin (CIT)) production, respectively. Wheat kernels were inoculated with one strain of each species during a solid-state fermentation followed over 63 days. Different growth and extrolite production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…CIT was found at a concentration of up to 4.2 g/g, far exceeding the regulatory level of 2 μg/g established by the European Union (EU) when Monascus ruber is used for fermentation with wheat kernels as a solid substrate. 58 Thirty-seven red yeast rice dietary supplements, including pure red yeast rice, were purchased from the Internet and local Italian pharmacies for CIT analysis by Laura Righetti et al 59 They discovered that approximately 86% of the samples did not satisfy the maximum EU level for CIT and that several items labeled as CIT-free presented CIT contamination. Of the 31 commercial ingredients of red yeast rice supplements purchased in China, Avula et al found CIT in approximately one-third of the samples using liquid chromatography-accurate quadrupole time-of-flight mass spectrometry.…”
Section: Cit Contamination Caused Bymentioning
confidence: 99%
See 1 more Smart Citation
“…CIT was found at a concentration of up to 4.2 g/g, far exceeding the regulatory level of 2 μg/g established by the European Union (EU) when Monascus ruber is used for fermentation with wheat kernels as a solid substrate. 58 Thirty-seven red yeast rice dietary supplements, including pure red yeast rice, were purchased from the Internet and local Italian pharmacies for CIT analysis by Laura Righetti et al 59 They discovered that approximately 86% of the samples did not satisfy the maximum EU level for CIT and that several items labeled as CIT-free presented CIT contamination. Of the 31 commercial ingredients of red yeast rice supplements purchased in China, Avula et al found CIT in approximately one-third of the samples using liquid chromatography-accurate quadrupole time-of-flight mass spectrometry.…”
Section: Cit Contamination Caused Bymentioning
confidence: 99%
“…Recently, human health and intake safety have received increasing attention, and the control of functional products in various countries has increased, alleviating CIT contamination in red yeast rice dietary supplements. CIT was found at a concentration of up to 4.2 g/g, far exceeding the regulatory level of 2 μg/g established by the European Union (EU) when Monascus ruber is used for fermentation with wheat kernels as a solid substrate . Thirty-seven red yeast rice dietary supplements, including pure red yeast rice, were purchased from the Internet and local Italian pharmacies for CIT analysis by Laura Righetti et al They discovered that approximately 86% of the samples did not satisfy the maximum EU level for CIT and that several items labeled as CIT-free presented CIT contamination.…”
Section: Possible Contamination Of Cit In Monascus Cheesementioning
confidence: 99%